ANALISA KECEPATAN MOTOR PADA ALAT BANTU PENGELASAN BAHAN LEHER KNALPOT STAINLESS STEEL - Murod, Moh Iqbal; Sakti, Arya Mahendra (Universitas Negeri Surabaya, 2022)
In the manufacturing process, especially welding an object, there are still several obstacles, namely the quality of the welding results, besides depending on the welding work process it also depends on the selection of predetermined welding parameters so that the results obtained are very good. Therefore, every difference in welding speed is different as well as the results produced. So with the